Low to moderate dose 137Cs (γ) radiation promotes M2 type macrophage skewing and reduces atherosclerotic plaque CD68+ cell content in ApoE(−/−) mice - N. Rey; T. Ebrahimian; C. Gloaguen; D. Kereselidze; E. Christelle; C. Brizais; F. Bachelot; G. Riazi; V. Monceau; C. Demarquay; I. Garali Zineddine; D. Klokov; et al. (Scientific Reports, 2024)
Abstract The effects of low doses of ionizing radiation on atherosclerosis remain uncertain, particularly as regards the generation of pro- or anti-inflammatory responses, and the time scale at which such effects can occur following irradiation. To explore these phenomena, we exposed atheroprone ApoE(−/−) mice to a single dose of 0, 0.05, 0.5 or 1 Gy of 137Cs (γ) administered at a 10.35 mGy min−1 dose rate and evaluated short-term (1–10 days) and long-term consequences (100 days). Bone marrow-derived macrophages were derived from mice 1 day after exposure. Irradiation was associated with a significant skewing of M0 and M2 polarized macrophages towards the M2 phenotype, as demonstrated by an increased mRNA expression of Retnla, Arg1, and Chil3 in cells from mice exposed to 0.5 or 1 Gy compared with non-irradiated animals. Minimal effects were noted in M1 cells or M1 marker mRNA. Concurrently, we observed a reduced secretion of IL-1β but enhanced IL-10 release from M0 and M2 macrophages. Effects of irradiation on circulating monocytes were most marked at day 10 post-exposure, when the 1 Gy dose was associated with enhanced numbers of both Ly6CHigh and Ly6Low cells. By day 100, levels of circulating monocytes in irradiated and non-irradiated mice were equivalent, but anti-inflammatory Ly6CLow monocytes were significantly increased in the spleen of mice exposed to 0.05 or 1 Gy. Long term exposures did not affect atherosclerotic plaque size or lipid content, as determined by Oil red O staining, whatever the dose applied. Similarly, irradiation did not affect atherosclerotic plaque collagen or smooth muscle cell content. However, we found that lesion CD68+ cell content tended to decrease with rising doses of radioactivity exposure, culminating in a significant reduction of plaque macrophage content at 1 Gy. Taken together, our results show that short- and long-term exposures to low to moderate doses of ionizing radiation drive an anti-inflammatory response, skewing bone marrow-derived macrophages towards an IL-10-secreting M2 phenotype and decreasing plaque macrophage content. These results suggest a low-grade athero-protective effect of low and moderate doses of ionizing radiation.